Nanostructural mechanisms of physicochemical reactions - V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
It is generally accepted that physicochemical reactions are mainly molecular atomic. It was shown that liquid water consists of 12 % molecules and 88 % of ice nanocrystals. When melting, microcrystals of substances break down into nanocrystals and molecules or into nanocrystals and atoms. During the crystallization of liquids, the reverse process occurs. Based on the above physicochemical reactions, it is shown that nanostructural mechanisms prevail in their basis.